Literasi Keuangan sebagai Prediktor Perilaku Keuangan Mahasiswa: Tinjauan dari Sisi Kapasitas Pendapatan - Sihura, Clara Grace Cintya; Widagdo, Chrisostomus Susmono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to comprehensively investigate the influence of financial literacy and income on the financial management behavior of college students amidst massive economic digitalization. Employing an explanatory quantitative approach through a survey of 100 respondents , the data analysis procedure was conducted hierarchically, beginning with classical assumption tests to ensure the model’s status as a Best Linear Unbiased Estimator (BLUE), followed by multiple linear regression techniques to measure the strength of the causal relationships between variables. The partial results indicate that financial literacy acts as a dominant predictor with a positive and significant effect, evidenced by a t-statistic value of 8.160 (p < 0.05). This confirms that a deep understanding of basic financial concepts, risk management, and the time value of money serves as a primary determinant of financial discipline. The income variable also shows a significant positive influence with a t-statistic of 2.987 (p < 0.05) , though its role is primarily as an economic facilitator that requires the support of literacy to prevent the